The Great War and the transformation of the Atlantic copper trade. Issue 3 (2nd September 2017) - Delaney, Nathan
ABSTRACT: Just before the First World War, 70% of the globe's copper was mined or processed in the U.S. At that time, nearly the same percentage of copper was consumed in Europe – the vast majority of which originated from American mines. At first glance, a trade dynamic of this sort would appear to strongly favour the position of U.S. producers; surprisingly, sources indicate that control of the world's copper trade was largely the prerogative of a select group of German metal trading companies – the largest and most influential among them was Metallgesellschaft (MG). The following essay explores the competitive dynamics among producers, consumers, and intermediary groups. It argues that U.S. producers were only able to gain substantive control over the supply and marketing of copper in the wake of the economic disruption caused by the Great War.